Regio‐ and Diastereoselective Copper‐Catalyzed Carbomagnesiation for the Synthesis of Penta‐ and Hexa‐Substituted Cyclopropanes. Issue 21 (14th April 2021) - Cohen, Yair; Augustin, André U.; Levy, Laura; Jones, Peter G.; Werz, Daniel B.; Marek, Ilan
Abstract: Despite the highly strained nature of cyclopropanes possessing three vicinal quaternary carbon stereocenters, the regio‐ and diastereoselective copper‐catalyzed carbomagnesiation reaction of cyclopropenes provides an easy and efficient access to these novel persubstituted cyclopropyl cores with a complete regio‐ and diastereoselectivity. Abstract : Despite the highly strained nature of cyclopropanes possessing three vicinal quaternary stereocenters, the regio‐ and diastereoselective copper‐catalyzed carbomagnesiation reaction provides an easy and efficient access to these novel persubstituted cyclopropyl cores with a complete regio‐ and diastereoselectivity.